Minat Membaca dan Implementasinya dalam Bimbingan dan Konseling - Marimbun Marimbun (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2019)
Reading interst is a strong desire that accompanied a sense of pleasure of enjoyment of reading with self-will. Reading is a demand for individuals because reading is an effective activity to gain insight and knowledge. Surah Al-Alaq which is the first letter to come down is a reading order. Furthermore, the mandate of regulations and legislation also invites reading culture and encourages people to enjoy reading. The problematics of some of the research results indicate that Indonesian interest in reading is still relatively low. Therefore how important are efforts to foster interest in reading. Improving interest in reading must be done through families, education units and the community. One of the factors influencing reading interest is the teacher. Counseling teacher/ Counselor is a teacher assigned to carry out guidance and counseling activities in schools responsible for providing various service activities in developing various student potentials and encouraging national education goals. Guidance counseling at schools is expected to be more intensive in order to improve students interest in reading through various types of counseling services. As for some services that can be applied in improving interest in reading such as orientation services, information, group guidance and individual counseling.